Improving Civics Learning Activity and Outcomes Through the Role Playing Model - Endah Sri Peni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to find out the role playing learning model can increase learning activity and to find out through the role playing model can improve learning outcomes in class IV semester I SD Negeri 01 Jatirejo in the 2021/2022 academic year. This research is a classroom action research using data collection techniques, tests, observations, and documentation. The data analysis technique uses a comparative descriptive technique. The research procedure includes: the planning stage, the action stage, the observation stage, the reflection stage. The results of the study: (1) there is an increase in learning activity. Before the study, learning activity was 35.71% (low), cycle I was 51.48% (medium), and in cycle II it increased to 80.88% (high). (2) increase in learning outcomes. Before the research, the percentage of completeness of student learning outcomes was 28.57% (6 students); cycle I 42.85% (9 students), cycle II 90.47% (19 students). (3) the implementation of the role playing model went well with an average score of 60.71% (good) in the first cycle, and increased with an average score of 91.06% (very good) in the second cycle.